iTRAQ Proteomic Analysis Reveals That Metabolic Pathways Involving Energy Metabolism Are Affected by Tea Tree Oil in Botrytis cinerea - Xu, Jiayu; Shao, Xingfeng; Wei, Yingying; Xu, Feng; Wang, Hongfei (Frontiers in Microbiology, 2017)
Tea tree oil (TTO) is a volatile essential oil obtained from the leaves of the Australian tree Melaleuca alternifolia by vapor distillation. Previously, we demonstrated that TTO has a strong inhibitory effect on Botrytis cinerea. This study investigates the underlying antifungal mechanisms at the molecular level. A proteomics approach using isobaric tags for relative and absolute quantification (iTRAQ) was adopted to investigate the effects of TTO on Botrytis cinerea. A total of 718 differentially expression proteins (DEPs) were identified in TTO-treated samples, 17 were markedly up-regulated and 701 were significantly down-regulated. Among the 718 DEPs, 562 were annotated and classified into 30 functional groups by GO (gene ontology) analysis. KEGG (Kyoto Encyclopedia of Genes and Genomes) enrichment analysis linked 562 DEPs to 133 different biochemical pathways, involving glycolysis, the tricarboxylic acid cycle (TCA cycle), and purine metabolism. Additional experiments indicated that TTO destroys cell membranes and decreases the activities of three enzymes related to the TCA cycle. Our results suggest that TTO treatment inhibits glycolysis, disrupts the TCA cycle, and induces mitochondrial dysfunction, thereby disrupting energy metabolism. This study provides new insights into the mechanisms underlying the antifungal activity of essential oils.